2018
DOI: 10.1021/acsomega.8b00980
|View full text |Cite
|
Sign up to set email alerts
|

Single-Pot Reductive Rearrangement of Furfural to Cyclopentanone over Silica-Supported Pd Catalysts

Abstract: Direct one-pot hydrogenation of furfural (FFR) to cyclopentanone (CPO) was investigated over different silica-supported Pd catalysts. Among these, 4% Pd on fumed silica (4%Pd/f-SiO 2 ) showed remarkable results, achieving almost 98% furfural (FFR) conversion with ∼89% selectivity and 87% yield to cyclopentanone at 165 °C and 500 psig H 2 pressure. More interestingly, the fumed-silica-supported catalyst tuned the selectivity toward the rearrangement product, i.e., c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…1 [16,30]. In fact, the selectivity of THFalc was remained unchanged at relatively higher reaction temperature or longer reaction time.…”
Section: Entrymentioning
confidence: 95%
See 1 more Smart Citation
“…1 [16,30]. In fact, the selectivity of THFalc was remained unchanged at relatively higher reaction temperature or longer reaction time.…”
Section: Entrymentioning
confidence: 95%
“…By using similar Pt/NC-BS catalyst, Liu et al reported that maximum yield of CPO (76%) was obtained from FFald at 150 °C and 3.0 MPa H2 [15]. Date et al reported that efficient reductive rearrangement of furfural using Pd/SiO2 catalyst resulted cyclopentanone with 87% yield (at 98% conversion of FFald) at 165 °C and 5 MPa H2 [16]. However, precious metals, such as Au, Ru, Pd, and Pt were utilized in these catalyst systems.…”
Section: Introductionmentioning
confidence: 99%
“…The Pd/Al 2 O 3 and Pd/TiO 2 catalysts showed similar results in that the CPO selectivity decreased or changed slightly. Nandan et al reported that the Lewis acid sites of PdO affect the rearrangement of FAL to CPO [32]. Based on the XPS results, the Pd 2+ /Pd ratio of the Pd/TiO 2 catalyst was lower than that of the Pd/Al 2 O 3 catalyst.…”
Section: Hydrogenation Of Furfuralmentioning
confidence: 99%
“…In Scheme 2 the reported catalytic rearrangement of FAL to CPO is depicted. [47] Initially, FAL is hydrogenated towards FURÀ OH over the active sites of the metal. Afterwards, the water molecules attack via the fifth position of the furan ring to form the oxycation.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…[36][37][38][39][40] Particular focus has been put on the transformation of furfural to aliphatic cyclic molecules such as cyclopentanone and cyclopentanol because they are important intermediate in fine chemical industry with a broad range of application in the perfume, medicine, and agriculture field. [40,41] Several catalytic studies (Table S1, supplementary material) have been focusing on the effect of the active phase, [42][43][44] metal content, [34] nature of the catalytic support [34,[45][46][47] and the reaction media, [48] among others. In this regard, Jia et al [49] studied the aqueous phase hydrogenation of furfural to cyclopentanone over NiFe-supported catalysts.…”
Section: Introductionmentioning
confidence: 99%